Three new species of chewing lice of the genus Emersoniella Tendeiro, 1965 (Insecta: Phthiraptera: Ischnocera: Philopteridae) from Papua New Guinean kingfishers and kookaburras (Aves: Coraciiformes: Alcedinidae) - Gustafsson, Daniel R.; Bush, Sarah E. (Zootaxa, 2014)
Three new species of the ischnoceran louse genus Emersoniella (Phthiraptera) are described from four species of New Guinean kingfishers and kookaburras (Coraciiformes: Alcedinidae: Halcyoninae). They are: Emersoniella crassicarina n. sp. ex Dacelo gaudichaud Quoy & Gaimard (rufous-bellied kookaburra) and Dacelo leachii intermedia Salvadori (blue-winged kookaburra); E. reninoda n. sp. ex Melidora macrorrhina macrorhina Lesson (hook-billed kingfisher); and E. persei n. sp. ex Tanysiptera danae Sharpe (brown-headed paradise-kingfisher). In addition, we illustrate Emersoniella regis Emerson & Price, Emersoniella halcyonis Tendeiro, and the male genitalia of Emersoniella galateae Emerson & Price, as well as provide a complete host-louse checklist, and an updated key to all seven species of this genus.